THE DESIGN OF TECHNICAL FACILITIES REVIEW FOR TRAINING SPECIALISTS OF RAILWAY TRANSPORT - Myamlin, S. V.; Blokhin, Ye. P.; Zhyzhko, V. V.; Pysmennyi, Ye. O. (Science and Transport Progress, 2006)
In article varies types of simulators for training of specialists of railway transport analyzed.